Performance Analysis of Half-Sweep Successive Over-Relaxation Iterative Method for Solving Four-Point Composite Closed Newton-Cotes Quadrature System - Muthuvalu, M.; Htun, T.; Aruchunan, Elayaraja; Sulaiman, J. (2017)
© 2016 IEEE. The theory and application of integral equations is an important subject within applied mathematics. Consequently, the main aim of this research paper is to investigate the performance of a variant of Successive Over-Relaxation iterative method i.e. Half-Sweep Successive Over-Relaxation (HSSOR) for solving four-point composite closed Newton-Cotes quadrature (4-CCNC) system that generated from linear Fredholm integral equations of the second kind. The numerical results from the simulations of the tested methods are presented.